The impact of school periods and long holiday periods on the occurrence of neurally mediated syncope in children - Shuo Wang; Ping Liu; Xiaohui Gong; Jizhi Xu; Tuoyu Gan; Yuwen Wang; Hong Cai; Runmei Zou; Cheng Wang (BMC Pediatrics)
Abstract Objective To explore the impact of school periods and long holiday periods on the occurrence of neurally mediated syncope (NMS) in children. Methods A retrospective analysis was conducted on 262 children with NMS. The children were aged 4–17 years, 119 males. 244 cases were diagnosed as vasovagal syncope, and 18 cases as postural orthostatic tachycardia syndrome. The data on the age, sex, syncope triggers, hemodynamic types, family history of syncope of children with syncope during long holiday periods group (n = 68) and school periods group (n = 194) were compared. Results (1) Incidence of syncope: The incidence of syncope during school periods (74.05%) was higher than that during long holiday periods (25.95%). (2) Comparison of sex and triggers: The constituent ratio of females with syncope during school periods was higher than that of males (P < 0.05). Among the triggers, the proportion of sudden postural change during long holiday periods was higher than that during school periods (26.47% vs. 21.13%, P < 0.05). (3) Univariate analysis: Situational syncope was a potential protective factor when syncope occurred during school periods (OR 0.23, 95%CI 0.07–0.76, P < 0.05), and being female was a potential risk factor (OR 1.92, 95%CI 1.10–3.35, P < 0.05). (4) Comparison of multiple models: In the risk of syncope occurring during school periods, situational syncope reduced the risk by 79% compared with no trigger, and being female increased the risk by 78% compared with being male. Conclusions The occurrence of NMS-related syncope events in children is associated with school periods and long holiday periods. During school periods, being female is a risk factor for syncope, while situational syncope is a protective factor.